IDENTIFIKASI PENCAPAIAN LITERASI ENERGI PESERTA DIDIK PADA PEMBELAJARAN BERBASIS STEM DENGAN BANTUAN SIMULASI PhET - Musawwir Usman; Akhmad Syakur; Nur Rahmah Sangkala (Universitas Cokroaminoto Palopo, 2025)
Innovations in science education continue to develop, one of which is STEM-based learning. This learning can be combined with virtual laboratory media, such as the PhET simulation, which can develop students' skills. Currently, the students' skills that can deal with energy problems that occur in Indonesia are energy literacy. Therefore, this study aims to identify students' energy literacy achievement in STEM-based learning with PhET simulations. This study is a quasi-experiment with a one-group posttest-only design. The sample in this study was 127 selected by random sampling technique. The data analysis technique used is descriptive quantitative to analyze and determine students' energy literacy achievement category. The results indicate that STEM-based learning with PhET simulations is able to train students' energy literacy to a good category with an average value of 71.74 with details of cognitive domains of 52, affective of 85.33, and behavioral of 78. This is due to STEM-based learning with PhET simulations allows students to be more active and creative in understanding concepts, especially those that are more abstract. The aspects most influenced by STEM-based learning with PhET simulations are basic energy knowledge in the cognitive domain, responsibility in the affective domain, and energy-saving behavior in the behavioral domain.